TINJAUAN YURIDIS PENEGAKAN HUKUM TINDAK PIDANA KORUPSI APBD YANG DILAKUKAN OLEH KEPALA DAERAH DI LAMPUNG TENGAH - Wafi Rizqullah H; M Farhan Frans Putra, Shalsabila Hellenia, Rizki Rizaldi, Gusti Weliyansyah (INTELIGENSIA MEDIA, 2024)
Indonesia is a country of law, which means all the legal rules that apply in it The Indonesian state must be obeyed by citizens and state administrators. However, In fact, there are still many legal rules that are violated by citizens and state officials, such as in cases of criminal acts of corruption. Corruption crimes in Indonesia is very rampant from year to year. Therefore, it is needed enforcement of the law on criminal acts of corruption in order to realize its enforcement supremacy of law, upholding justice and realizing peace in life in public. However, it is very worrying that law enforcement is a criminal act Corruption in Indonesia is classified as very weak. This can be seen from the fact that there are still many regulators or law enforcers themselves who commit criminal acts of corruption. In Indonesia, the handling of corruption cases is carried out by state law enforcement agencies, including the Indonesian National Police, the Prosecutor's Office, the Corruption Eradication Commission (KPK), the Judiciary (Corruption Crime Court). This handling is carried out to protect the state budget with the aim of ensuring that the budgeted allocation of funds is not misused. The government issues legal products such as the Criminal Code (KUHP) and other laws that regulate the prevention, eradication and law enforcement of criminal acts of corruption. Eradicating corruption is said to be effective when the applicable laws and regulations succeed in making the perpetrators of corruption receive appropriate punishment and are able to be held accountable for their actions. The research method uses a normative and empirical juridical approach. The type of data used is secondary data and primary data. Data collection is through library research (library research) and field research. The data analysis used is qualitative juridical.